Concerning the study of the genre of epopee in modern literary criticism - Ivinskis, P. (Literatūra, 1974)
The generally accepted definition of epopee, as a literary work depicting the life of a nation at a turning-point of its history, indicates the main features of this genre of prose but it is not sufficiently defined historically. As a rule, any attempt to make this definition more precise by investigating the form of epopee, the epic tradition and the method of its creation inevitably leads either to a considerable limitation in the number of works of world literature of this type or to overabstract formulae adding little to the current definition. The author of this paper suggests the genre of epopee to be investigated on the basis of its content, i.e., according to the type of interrelations between hero and history, personality and people. The approach suggested allows tracing two main historic forms of epopee in the literature of the 19th-20th centuries along with the heroic epos of antiquity, i.e.: 1) the novel-epopee of critical and socialist realism revealing the social split of the nation and the necessity of doing away with it, and 2) the socialist epopee taking shape in the Soviet literature of the recent few decades and revealing the dialectics of joint efforts both of individual and society while making the new history. The peculiar poetics dealt with in the paper corresponds to the two main historic forms of the epopee of the 19th-20th centuries.